2022
DOI: 10.3389/fphys.2022.1027811
|View full text |Cite
|
Sign up to set email alerts
|

The influence of short sprint performance, acceleration, and deceleration mechanical properties on change of direction ability in soccer players—A cross-sectional study

Abstract: The study investigated the relationship between short sprint performance and mechanical parameters obtained during the acceleration and deceleration tasks with the change of direction (COD) performance in female and male soccer players. The acceleration and deceleration ability were compared in the “High/Fast” versus “Low/Slow” COD performance group based on a median split analysis in each sex group. One hundred three French soccer players were assessed for the sprinting Force-Velocity (F-V) profile (i.e., the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(60 reference statements)
0
2
1
Order By: Relevance
“…However, our results showed that mechanical variables derived from FVP and horizontal deceleration do not significantly explain the variance of performance in the CODA test. Our results do not agree with our hypothesis and align with similar results that found low relationships between mechanical variables and female soccer players' ability to change direction [60]. The FVP profile only identifies horizontally applied force during maximum speed rather than specific braking forces (i.e., horizontal and vertical forces) relevant during COD.…”
Section: Mechanical Variablescontrasting
confidence: 92%
“…However, our results showed that mechanical variables derived from FVP and horizontal deceleration do not significantly explain the variance of performance in the CODA test. Our results do not agree with our hypothesis and align with similar results that found low relationships between mechanical variables and female soccer players' ability to change direction [60]. The FVP profile only identifies horizontally applied force during maximum speed rather than specific braking forces (i.e., horizontal and vertical forces) relevant during COD.…”
Section: Mechanical Variablescontrasting
confidence: 92%
“…Generally speaking, one aspect of change-in-direction performance that has historically received less attention within the realm of sports science is the quantification of horizontal deceleration performance, including kinematic measures that go well beyond mere completion times in 5-0-5 and/or 5-10-5 tests [11]. In recent years, more attention has been dedicated to the importance of measuring and enhancing athletes' deceleration qualities [11,[14][15][16][17][18]. For instance, Graham-Smith et al [17] have investigated the links between the percentage of maximum speed attained with acceleration and stopping distance, which may help set realistic conditions for acceleration-deceleration drills and tests.…”
Section: Introductionmentioning
confidence: 99%
“…In sports science, there is a common research thread that investigates the relationship between acceleration and various physical measurements. See for example, Zhang et al, 2 Loturco, 3 Yildiz et al 4 and Little and Williams. 5 In this paper, we study maximum acceleration for players in soccer.…”
Section: Introductionmentioning
confidence: 99%